اثر استخدام الحاسوب في تدريس اللعة الانجليزية في تحصيل طالبات الصف الثامن الاساسي وتحسين دافعيتهن نحو التعلم - الرمحي، ديما محمد اسعد; الوريكات، منصور أحمد (عمان, 2015)
This study aimed to investigate the effect of using computer in teaching English language on promoting 8th grade students' achievement and improving their motivation towards learning. The study followed the quasi- experimental design. The sample of this study consisted of (48) female students of 8th basic grade of Al-Jazeera School in Amman. Two groups were purposely chosen; one of them was the experimental group, which consisted of (24) students, was taught via computer. The other was the control group, which consisted of (24) students, was taught with the traditional approach (without using computer). Both validity and reliability of the study tools were tested. To achieve the objectives of the study, the researcher developed educational English language computerized software for 8th basic grade. The researcher also constructed a (30) item achievement test (objective test), in addition to constructing a (26) item motivational scale. The results showed a statistically significant differences in students' achievement in English language achievement test, in favor of the experimental group students, and there are also statistically significant differences in student's motivation towards learning in favor of the experimental group students. Based upon these results, the researcher recommended using computer in teaching English language because of its role in increasing educational motivation of students towards learning and improving their educational achievement. In addition, the researcher recommended making more studies investigating the effect of using computer on English language skills on the same grade.
Keywords: تكنولوجيا التعليم -- التعليم بالحاسوب -- تدريس اللغة الانجليزية -- تقييم الاداء -- طلاب الصف الثامن الاساسي -- الدافعية للتعلم